Pedagogy of scientific research in higher university education - Ruiz-Aquino, Mely (2025)
University higher education is essential to create the intellectual conditions that allow the generation and use of scientific knowledge, and permanent and sustainable learning of people, contributing to the resolution of problems and / or needs, in this scenario the teaching of scientific research is part of the mission and vision of all universities, according to this, scientific research is a fundamental function of the university; This is a very important element in the process of educational quality because through it scientific knowledge is generated and learning is fostered for the generation of new knowledge; in addition, scientific research links the university with society.